30 years of solitary confinement: what has changed, and what still needs to happen - Sharon Shalev (Torture)
Solitary confinement cells are where those considered to be too dangerous to themselves or to others, too troublesome, too mentally unwell, or simply different, will be locked away, spending 22-24 hours a day alone, out of sight and out of mind.